An inventory decision-making model considering continuous production and detection of electric energy metering device. (2018) - Bian, Wenliang; Yang, Haifeng; Sun, Yao; Xie, Yan
This paper studies the inventory decision problem of power metering device under the condition of continuous production testing. Using the theory of constraints (TOC) to identify bottlenecks existing in the production test system, and then through the establishment of integer programming model, the research focuses on the initial inventory optimisation decision-making of inspection device and checked device in a week. According to the practical decision-making situations, this paper researches the in-out warehouse and vehicle scheduling constraints such as time window; under the condition of continuous operation, it optimises the total cost of inventory and vehicle scheduling. Then we use Matlab software to analyse the model, and use the Flexsim software to simulate the process of testing. In this paper, the research for inventory control of measuring centre with continuous production line provides the beneficial reference for power grid enterprises.